Review on the ethnomedicinal, phytochemical and pharmacological properties of Piper sarmentosum: scientific justification of its traditional use - Zarizal, Suhaili; Atefeh, Seyyedan; Farhana, Yahya (2013)
Piper sarmentosum is a creeping herb belongs to the family of Piperaceae. It is locally known to the Malays as ‘Pokok kadok’ and can be found in different regions of South-East Asia including Malaysia. Ethnopharmacologically, various parts of the plant (e.g. leave, fruit and root) are widely used in Asian countries for centuries to treat different types of diseases and ailments such as hypertension, diabetes, joint aches, muscle pain, coughs, influenza, toothaches and rheumatism. Scientific findings also demonstrated different pharmacological actions of various parts of P. sarmentosum such as adulticidal, antitermite, antioxidant, antifungal, antituberclosis, antiplasmoid, antimalarial, hypoglycemia, antiinflammatory, antinoceptive, antipyretic, antibacterial, anticancer, antituberculosis, antiangiogenesis, antimicrobial, antifeedant and cytotoxic activities. Different types of phytochemical constituents have been successfully identified and isolated from various parts of P. sarmentosum. Therefore, the information related to the botany, ethnomedicinal uses, phytochemical constituents and pharmacological activities of P. sarmentosum were reviewed here.